Economic incentives for biodiversity conservation: What is the evidence for motivation crowding? - Julian Rode; Erik Gómez-Baggethun; Torsten Krause (Helmholtz-Zentrum für Umweltforschung (UFZ), 2013)
As economic incentives for biodiversity and ecosystem service protection (e.g., payments for ecosystem services) have become widespread in environmental science and policy, a major concern among conservationists and environmental scientists is that economic incentives may undermine people's intrinsic motivations to conserve biodiversity. In this paper we review the theoretical insights and empirical findings on motivation crowding effects with economic instruments for biodiversity protection. First, we synthesize the psychological mechanisms behind motivation crowding effects relevant for environmental behavior as identified in the specialized literature. We then conduct a systematic review of the empirical evidence. Our results show that, although several empirical studies suggest the existence of crowding-out and crowding-in effects, evidence remains inconclusive due to i) methodological limitations for empirical studies to demonstrate crowding effects, ii) lack of adequate baseline information about pre-existing intrinsic motivations, iii) weak comparability of results across case studies resulting from inconsistent terminology and methods, and iv) the complexity stemming from cultural and contextual heterogeneity. We conclude that, as economic instruments for conservation are increasingly implemented, it becomes paramount to develop robust methodologies for assessing pre-existing intrinsic motivations and changes in people's motivational structures. To address possible detrimental long term effects for conservation outcomes we call for caution in situations where high uncertainties remain.
Keywords: 330; biodiversity; policy instruments; economic incentives; motivation crowding